ENVISIONING OPEN-AIR MUSEUM FOR INDONESIAN - Yusfan Adeputera Yusran (Dimensi: Journal of Architecture and Built Environment, 2018)
The founding of Skansen in the early of the 19th century was a milestone behind the phenomenon of Open-air museums all over the world. Although late, this phenomenon began to emerge in Indonesia since 1972 marked by the establishment of Taman Mini Indonesia Indah (TMII). Behind all the controversy on its establishment, TMII has been recognized as one of the nation pride as well as the first instituted open-air museum in the country. Ahead, this noble purpose should be further envisaged as an opportunity for Indonesian to take a part in rescuing remaining vernacular houses as the provision for future generations recognize their identity. By observing TB Silalahi Center in Balige and Taman Nusa in Gianyar, this paper describes that the opportunity for Indonesian to conserve ex-situ their neglected vernacular houses also definitely could be realized. From the analysis, some constraint found in terms of management, specifically in financial issue, but proven does not make a significant barrier in making these both museums keep running. Need collaboration from related parties since there is no proper translocation procedure done and also the weaknesses of tangled documentation. This concern aroused in order to prospecting ex-situ conservation for Indonesian vernacular houses properly implemented as an Open-air museum.